2014
DOI: 10.1080/14786435.2014.976287
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the discrepancy between the variation of the physical properties of Ce1-xYbxCoIn5single crystals and thin films with Yb composition

Abstract: The extraordinary electronic phenomena found in the Ce 1--x Yb x CoIn 5 system have attracted much interest. These phenomena include an Yb valence transition, a change in Fermi surface topology, and suppression of the heavy fermion quantum critical field at a nominal concentration x ≈ 0.2, which, surprisingly, have no discernable effect on the unconventional superconductivity and normal--state non--Fermi liquid behavior that occur over a broad range of x up to ~0.8. However, the variation of the coherence temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 28 publications
6
21
0
Order By: Relevance
“…This suggests that our determination of the actual Yb concentrations for our single crystals is accurate, and further confirms the conclusion of Ref. [18]. According to Ref.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…This suggests that our determination of the actual Yb concentrations for our single crystals is accurate, and further confirms the conclusion of Ref. [18]. According to Ref.…”
supporting
confidence: 76%
“…Recently, the anomalous phenomena observed in Ce 1−x Yb x CoIn 5 system have attracted much attention [16][17][18][19][20][21][22][23][24][25][26]. At first, the violation of Vegard's law was found in Ce 1−x Yb x CoIn 5 single crystals, together with the robustness of T c and Kondocoherence temperature T coh upon Yb doping [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These crystals have a nominal Yb doping x nom = 0.2 and an actual doping x act = 0.07. The crystal structure and unit cell volume were determined from X-ray powder diffraction measurements, while the actual composition was determined according to the method developed by Jang et al 24 Since all previous publications on this system give the nominal Yb concentration instead of the actual concentration, in this paper we use the nominal concentrations whenever referring to the results of earlier publications in order to be consistent with their reports, while we use the actual Yb concentration when we refer to the present work. We note that the study by Jang et al 24 has shown that x act ≈ 1 3 x nom , providing that the nominal Yb doping is less than about 40 %.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of the linear term in MR is a sign of broken inversion symmetry of the system. There is some recent calculations [40][41][42][43][44][45] which also reveals similar behaviour. …”
Section: Discussion Of Resultsmentioning
confidence: 56%